Staquorsin: A Novel Staphylococcus aureus Agr-Mediated Quorum Sensing Inhibitor Impairing Virulence in vivo Without Notable Resistance Development - Mahdally, Norhan H.; George, Riham F.; Kashef, Mona T.; Al-Ghobashy, Medhat; Murad, Fathia E.; Attia, Ahmed S. (Frontiers in Microbiology, 2021)
The emergence of microbial resistance to the available antibiotics is a major public health concern, especially with the limited rate of developing new antibiotics. The utilization of anti-virulence agents is a non-conventional approach that can be used to combat microbial infection. In Staphylococcus aureus, many virulence factors are regulated by the Agr-mediated quorum sensing (QS). We developed a chemical compound that acts a potential Agr-inhibitor without reducing bacterial viability. The compound was designated staquorsin for Staphylococcus aureus quorum sensing inhibitor. In silico analyses confirmed the binding of staquorsin to the AgrA active site with an absolute binding score comparable to savirin, a previously described AgrA inhibitor. However, staquorsin turned out to be superior over savarin in not affecting the S. aureus viability in concentrations up to 600 µM. On the other hand, savirin inhibited S. aureus growth in concentrations as low as 25 µM. Moreover, staquorsin proved to be a potent inhibitor of the Agr system by inhibiting hemolysins, lipase production, and affecting biofilms formation and detachment. On the molecular level it significantly inhibited the effector transcript RNA III. In vivo testing, using the murine skin abscess model, confirmed the ability of staquorsin to modulate S. aureus virulence by effectively controlling the infection. Twenty passages of S. aureus in the presence of 40 µM staquorsin have not resulted in loss of activity as evidenced by maintaining its ability to reduce hemolysin production and RNA III transcript levels. In conclusion, we hereby describe a novel anti-virulence compound inhibiting the S. aureus Agr-system and its associated virulence factors. It is active both in vitro and in vivo, and its frequent use does not lead to the development of resistance. These findings model staquorsin as a promising drug candidate to join the fierce battle against the formidable pathogen S. aureus.